Learning Italian language: when you want, when you are free and from the place you prefer / Piermauro Catarinella and Mohd Ridzuan Abdul Malek - Catarinella, Piermauro (Dr.); Abdul Malek, Mohd Ridzuan (Universiti Teknologi MARA Shah Alam, 2018)
Sometimes it is difficult to find the time to attend a language course that we are interested to learn. This is true especially for those who are working. The objective of this new program is to allow everyone to choose the best time to study without having to follow a certain tight schedule. It could be in the morning, in the afternoon, at night, during weekdays or even on public holidays. The novelty of this tool will allow one to study Italian language at a comfortable place of one’s choice (home, office, car). What is required is only an internet connection. That’s all. This on line course is useful to anyone (kids, adults, old folks) who is interested to study the Italian language in a fun and easy way. Although this new Italian program is totally free, it has the potential to be sold in the market.